HIGH-DENSITY CONCRETE AS A RADIATION SHIELDING – SYSTEMATIC LITERATURE REVIEW - Prima Ranna; Oei Fuk Jin (Jurnal Infrastruktur, 2024)
High-density concrete (HDC) has been extensively employed as radiation shielding owing to its high density and capacity to absorb gamma rays and neutrons. The optimal average density of HDC for protecting against various types of radiation generally ranges from 2.2 g/cm³ to 3.5 g/cm³. This density may vary depending on the type of aggregate used, such as serpentine, barite, siderite, magnesite, and others. The study analyzes the use of high density concrete as a radiation protector using systematic literature review. The research method uses the PRISMA methodology with data search using the Publish or Perish (PoP) application with the keywords